Pemanfaatan Perpustakaan Sekolah Sebagai Pusat Sumber Belajar di Sekolah Dasar Negeri 23 Painan Utara - Novriliam, Rio; Yunaldi, Yunaldi (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
This research aims to describe (1) the level of use of the school library as a learning resource center elementary school students Painan 23 North, (2) The school library which includes a collection of libraries, library collections and processing, library services, facilities and infrastructure perpustakaanSD N 23 North Painan as a learning resource center. Writing this using qualitative methods, analyzing the data carried by describing and explaining data. Data were collected by interview and observation. Based on data analysis, it can be concluded. (1) the existence of SD State Library 23 North Painan as a learning resource center is still not optimally utilized by teachers and students, (2) implementation of the Elementary School Library 23 North Painan not optimal, because the collection is owned by the SD State 23 North Painan still minimal. Processing the collection has been done although not optimal because there is a special librarians administer libraries yan. Library services are still constrained by the short time the library is open at rest. While the elementary school library Painan 23 North has a good infrastructure, but has not been fully utilized.Keywords: utilities; learning resource center